Urgensi Kebijakan Pendanaan Jaminan Kesehatan Masa Pandemi Covid-19 di Indonesia Menurut Undang - Undang Nomor 40 Tahun 2004 Tentang Sistem Jaminan Sosial Nasional (SJSN) - Kusuma Putri, Novi Eka; Monica Vita Agustin,; Muhammad Kuswanto,; Ni Wayan Wiwin Oktori, (Perspektif Hukum, 2022)
The purpose of this study is to determine the urgency of the health insurance funding policy during the Covid-19 pandemic in Indonesia according to Law Number 40 of 2004 concerning the National Social Security System (SJSN) and the implementation of the National Health Insurance in Indonesia in terms of funding aspects during the Covid-19 pandemic. after the issuance of Presidential Regulation Number 64 of 2020. The results of the study show that: 1) The urgency of the health insurance funding policy during the Covid-19 pandemic in Indonesia according to Law Number 40 of 2004 is the fulfillment of the implementation of health insurance that is affordable by all Indonesians fairly and evenly to realize prosperity in accordance with the Act. To reduce the burden and impact of the Covid-19 pandemic, the Government and the community must work together in building a strong national health system through financial support in the form of contributions as has been formulated and determined. 2) The issuance of Presidential Regulation Number 64 of 2020 was carried out during the Covid-19 pandemic which was endemic, the government was more present in the regulation. Most of the around 80% of the participants are guaranteed by the government.